Forum on Robert B. Pippin, "After the beautiful" - ed. by M. Farina, with R.B. Pippin, M. Farina, F. Campana, F. Iannelli, T. Pinkard, I. Testa, L. Corti (Lebenswelt: Aesthetics and Philosophy of Experience, 2016)
___